Programa de estágio extracurricular teórico-prático interdisciplinar de iniciação em oncologia - SILVA, José Henrique Santos (Universidade Federal do Pará, 2023)
From the identification of existing gaps in early learning stages of Health professionals to act upon the field of Oncology, this research sought to respond the focus question “How to assist in the training of undergraduates in the area of Health and sensitize them to work in the promotion, prevention, treatment, rehabilitation and palliation in oncology from an interdisciplinary perspective?”. To do so, the general objective was to “Structure an extracurricular internship program in Oncology for undergraduate students of courses in the area of Health in a theoretical-practical and interdisciplinary format of initiation in Oncology, based on the assumptions of active teaching-learning methodologies and interdisciplinary action”. This program was developed at the Instituição Oncológica do Brasil, a cancer research and treatment center located in Belém, Pará. Based on action research, the methodological path was divided into four phases: (i) carrying out a bibliographical survey; (ii) construction of the action plan; (iii) implementation of a pilot program; and (iv) follow-up of the investigation-action cycle. As an educational product resulting from the research, the “Guia didático: Programa de Estágio Extracurricular Teórico-Prático Interdisciplinar de Iniciação em Oncologia” was prepared, describing the structure of the Program (curricular organization, selection process, use of active teaching-learning strategies, evaluation process and others). The results obtained from the study also made it possible to verify the improvement in the training of undergraduates in the area of Health in terms of knowledge of Oncology subjects, which are scarcely addressed in the curricula of undergraduate courses. Because the Program is divided into axes (Teaching, Research and Extension), it provides a broader experience for the undergraduate student and the possibility of greater insertion in the Oncology specialty, expanding the vision of care and assistance in general. The division of the theoretical content into modules and the use of clinical cases makes teaching more focused on practical issues, related to the problems faced in the daily life of interdisciplinary assistance, providing the development of skills and competences for a differentiated support. Therefore, from the analysis of this experience, we believe that this developed product can favor and serve as an inspiration for the implementation of extracurricular internship programs in several other realities, whether or not in the area of Oncology – provided that the necessary adaptations are made and that the pedagogical proposals are similar.